Female Voice in Novel on The Jellicoe Road (2006) by Melina Marchetta - Gusti, Dilla Apri; Marlina, Leni (English Language and Literature, 2021)
AbstractThis study is aimed to seek how far novel On The Jellicoe Road (2006) by Melina Marchetta reflected the issues of female voice. Female voice refer to the character who was doing effort to get through her bad past and become a great person in the future. The young female character had been through difficult time that her age might be cannot do it. This analysis is related to feminist theory proposed by Abrams Kathryn (1999). The used of theory was based on the interpretation in the text and context of the novel. The data was collected from the quotation in the novel. The data collection were in the form of sentences and paragraphs. This research was descriptive and content analysis study. In this research, female voice examined the novel On The Jellicoe Road. The result of the study was the character have the ability to utilize her words, longing, and wishes of heart to improve her life. The main character choose to not let people around her take control of her life. The voice also showed that the character choose to deal with her childhood trauma. The main character showed that she can grown up as strong, independent and brave. In conclusion, the main character can show the world that female can also decide what she thought best for her and her life. She choose does not  want to under the control and turn her bad past into her strength.